Efficacy of native entomopathogenic nematode isolates and flubendiamide against the tomato leafminer, Phthorimaea (=Tuta) absoluta (Lepidoptera: Gelechiidae) and compatibility of the nematodes with flubendiamide - Laleh Ebrahimi; Edwin Lewis (Crop Protection, 2026)

Multi-component trail pheromones of the entomopathogenic nematodes Steinernema diaprepesi and Heterorhabditis bacteriophora - Alexander M. Gaffke; Jessica L. Griesheimer; Edwin E. Lewis; David Shapiro-Ilan; Fatma Kaplan; Hans T. Alborn (Journal of Invertebrate Pathology, 2026)

How does topography affect wind abrasion on Mars? Recently observed shifts in ventifact orientation at Gale crater - Daniel Y. Zhou; Madison L. Turner; William Rapin; Juergen Schieber; Amelie L. Roberts; Aster C. Cowart; Megan E. Hoffman; Bernard Hallet; Steve G. Banham; Deirdra Fey; Kevin W. Lewis; Sanjeev Gupta; et al. (Icarus, 2025)

Infection status of sugar beet plants influence infection decisions of root-knot and root lesion nematodes - Busra Sadic-Ulu; Tufan Can Ulu; Lucas Ripa; Glen Stevens; Edwin Lewis (Rhizosphere, 2025)

The duration of lithium use and biological ageing: telomere length, frailty, metabolomic age and all-cause mortality - Julian Mutz; Win Lee Edwin Wong; Timothy R. Powell; Allan H. Young; Gavin S. Dawe; Cathryn M. Lewis (GeroScience, 2024)
Lithium is an established first-line treatment for bipolar disorder. Beyond its therapeutic effect as a mood stabiliser, lithium exhibits potential anti-ageing effects. This study aimed to examine the relationship between the duration of lithium use, biological ageing and mortality. The UK Biobank is an observational study of middle-aged and older adults. We tested associations between the duration of lithium use (number of prescriptions, total duration of use and duration of the first prescription period) and telomere length, frailty, metabolomic age (MileAge) delta, pulse rate and all-cause mortality. Five hundred ninety-one individuals (mean age = 57.49 years; 55% females) had been prescribed lithium. There was no evidence that the number of prescriptions ( β = − 0.022, 95% CI − 0.081 to 0.037, p = 0.47), the total duration of use ( β = − 0.005, 95% CI − 0.023 to 0.013, p = 0.57) or the duration of the first prescription period ( β = − 0.018, 95% CI − 0.051 to 0.015, p = 0.29) correlated with telomere length. There was also no evidence that the duration of lithium use correlated with frailty or MileAge delta. However, a higher prescription count and a longer duration of use was associated with a lower pulse rate. The duration of lithium use did not predict all-cause mortality. We observed no evidence of associations between the duration of lithium use and biological ageing markers, including telomere length. Our findings suggest that the potential anti-ageing effects of lithium do not differ by the duration of use.

Enhancing entomopathogenic nematode efficacy with Pheromones: A field study targeting the pecan weevil - Jermaine D. Perier; Fatma Kaplan; Edwin E. Lewis; Hans Alborn; Paul Schliekelman; Michael D. Toews; Karl C. Schiller; David I. Shapiro-Ilan (Journal of Invertebrate Pathology, 2024)

Movers and shakers: Do nematodes that move more invade more? - Eddie K. Slusher; Edwin Lewis; Glen Stevens; David Shapiro-Ilan (Journal of Invertebrate Pathology, 2024)

Precision application of the entomopathogenic nematode Heterorhabditis bacteriophora as a biological control agent through the Nemabot - Hilal Erdoğan; Halil Ünal; İ. Alper Susurluk; Edwin E. Lewis (Crop Protection, 2023)

Building reactive copper centers in human carbonic anhydrase II - He Song; Andrew C. Weitz; Michael P. Hendrich; Edwin A. Lewis; Joseph P. Emerson (JBIC Journal of Biological Inorganic Chemistry, 2013)

Exploring substrate binding in homoprotocatechuate 2,3-dioxygenase using isothermal titration calorimetry - Kate L. Henderson; Vu H. Le; Edwin A. Lewis; Joseph P. Emerson (JBIC Journal of Biological Inorganic Chemistry, 2012)

Ecology in the service of biological control: the case of entomopathogenic nematodes - R. Gaugler; Edwin Lewis; Robin J. Stuart (Oecologia, 1997)